Process Evaluation of a Positive Youth Development Program in Hong Kong Based on Different Cohorts - Ben M. F. Law; Daniel T. L. Shek (The Scientific World Journal)
There are only a few process evaluation studies on positive youth development programs, particularly in the Chinese context. This study aims to examine the quality of implementation of a positive youth development program (the Project P.A.T.H.S.: Positive Adolescent Training through Holistic Social Programmes) and investigate the relationships among program adherence, process factors, implementation quality, and perceived program success. Process evaluation of 97 classroom-based teaching units was conducted in 62 schools from 2005 to 2009. Findings based on different cohorts generally showed that there were high overall program adherence and implementation quality. Program adherence and implementation process were highly correlated with quality and success of the program. Multiple regression analyses further showed that both implementation process and program adherence are significant predictors of program quality and success. Theoretical and practical implications of the findings are discussed.